READMISSION AND UNITED NATIONS ORGANIZATION - Beken , Аяна Токсанбаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
Readmission issues are mentioned in the artiсle at the UN level.